2014
DOI: 10.1002/2014gl060219
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of ambient and laboratory‐generated secondary organic aerosol

Abstract: The size and thickness of organic aerosol particles collected by impaction in five field campaigns were compared to those of laboratory-generated secondary organic aerosols (SOA). Scanning transmission X-ray microscopy was used to measure the total carbon absorbance (TCA) by individual particles as a function of their projection areas on the substrate. Particles with higher viscosity/surface tension can be identified by a steeper slope on a plot of TCA versus size because they flatten less upon impaction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(108 citation statements)
references
References 38 publications
5
103
0
Order By: Relevance
“…8b). This conclusion is consistent with work by O'Brien et al (2014) who also concluded that the viscosity of isoprene-derived particles is lower than the viscosity of α-pinene-derived particles based on the how much the particles flattened after impaction on a substrate. The differences may be due to a difference in the molecular weights of the two SOMs since viscosity can increase as the molecular weight of an organic compound increases (Zobrist et al, 2008;Koop et al, 2011).…”
Section: Comparison Of Viscosities Of Isoprene-derived Som and α-Pinesupporting
confidence: 91%
“…8b). This conclusion is consistent with work by O'Brien et al (2014) who also concluded that the viscosity of isoprene-derived particles is lower than the viscosity of α-pinene-derived particles based on the how much the particles flattened after impaction on a substrate. The differences may be due to a difference in the molecular weights of the two SOMs since viscosity can increase as the molecular weight of an organic compound increases (Zobrist et al, 2008;Koop et al, 2011).…”
Section: Comparison Of Viscosities Of Isoprene-derived Som and α-Pinesupporting
confidence: 91%
“…Despite the integral role of SOA in atmospheric processes, there remains a limited understanding of the chemical and physical changes induced in SOA as it is formed and subsequently aged. Understanding the physical state of SOA is especially important, as it can provide insight into SOA formation [12,13] and growth [14], gas-particle partitioning [15], reactive uptake on particle surfaces [16,17], and atmospheric impacts [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3c illustrates the heights of the ASOP as a function of particle size (determined as the two-dimensional (2D) projected area equivalent diameter), compared with other organic particles observed at the Southern Great Plains site and previously reported measurements 10 . For a given particle size, ASOP have total carbon absorption values up to ten times larger than particles observed in previous studies 10 . This indicates that ASOP are significantly more viscous (solid) than organic particles reported previously.…”
mentioning
confidence: 87%
“…Similarly sized carbonaceous particles with higher total carbon absorption are more viscous or solid (glassy) than those with lower absorption, which is indicative of liquid particles flattened on the substrate 10 . Figure 3c illustrates the heights of the ASOP as a function of particle size (determined as the two-dimensional (2D) projected area equivalent diameter), compared with other organic particles observed at the Southern Great Plains site and previously reported measurements 10 . For a given particle size, ASOP have total carbon absorption values up to ten times larger than particles observed in previous studies 10 .…”
mentioning
confidence: 99%